Knowledge of Cotton Growers about Integrated Weed Management Practices - A.T. Barkade , K.T.Lahariya , N.R. Koshti; D. M. Mankar (Indian Journal of Extension Education, 2017)
The present study was undertaken in Karanja and Manora Panchayat Samitis of Washim district in Vidarbha region of Maharashtra State. The findings revealed that majority of respondents belonged to middle age group ; educated up to college level; had middle family size (4 to 6 members), belonged to semi-medium size land holding category and agriculture was the main occupation, with annual income between of ` 1,00,001 to 2,00,000, had bi-seasonal cropping system, put up to 1.01 to 2.00 ha area under cotton crop; had medium sources of information; had medium category of extension contact; had medium level of economic motivation;, had medium level of knowledge and adoption of integrated weed management practices. As regards the correlation analysis, independent variables namely education, land holding, annual income, cropping pattern, area under cotton crop, sources of information, extension contact and economic motivation showed a positive and highly significant correlation with knowledge of the respondents at 0.01 level of probability. Whereas, the characteristics such as age, family size, occupation had shown negative and non contributory effect with knowledge of the respondents.